1990
DOI: 10.1002/ana.410280308
|View full text |Cite
|
Sign up to set email alerts
|

Polyneuropathy, ophthalmoplegia, leukoencephalopathy, and intestinal pseudo‐obstruction: POLIP syndrome

Abstract: We describe 5 individuals (from three separate families) with a progressive neurological disorder characterized by sensorimotor peripheral polyneuropathy, cranial neuropathies (external ophthalmoplegia, deafness), and the syndrome of chronic intestinal pseudo-obstruction. Magnetic resonance imaging showed widespread abnormality of the cerebral and cerebellar white matter in the 2 patients studied. Autopsy examination in 3 revealed widespread endoneurial fibrosis and demyelination in the peripheral nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 35 publications
2
42
0
1
Order By: Relevance
“…Wide spread supratentorial cortical atrophy was also pronounced in one study (Barragan-Campos et al, 2005). Postmortem studies have shown mild white matter edema or mild demyelination (Bardosi et al, 1987;Simon et al, 1990). …”
Section: Mitochondrial Neuro-gastro-intestinal Encephalomyopathymentioning
confidence: 89%
“…Wide spread supratentorial cortical atrophy was also pronounced in one study (Barragan-Campos et al, 2005). Postmortem studies have shown mild white matter edema or mild demyelination (Bardosi et al, 1987;Simon et al, 1990). …”
Section: Mitochondrial Neuro-gastro-intestinal Encephalomyopathymentioning
confidence: 89%
“…MNGIE (mitochondrial neurogastrointestinal encephalomyopathy), also known as POLIP (polyneuropathy, ophthalmoplegia, leukoencephalopathy, and intestinal pseudo-obstruction) or MEPOP (mitochondrial encephalomyopathy, polyneuropathy, ophthalmoplegia, and pseudo-obstruction) syndrome, is a condition characterized by moderate to severe sensorimotor polyneuropathy, ophthalomoplegia, and severe, sometimes fatal, GI dysmotility. 130,150,176 The initial presentation is usually of GI symptoms that include dyspepsia, bloating, eructation, cramps, intolerance of large meals, and episodic vomiting and diarrhea. Nonspecific white matter changes are seen in the cerebrum and cerebellum.…”
mentioning
confidence: 99%
“…In one report, all three studied patients had increased water content, reduced NAA, Cho and Cr and no lactate peaks in the areas of white matter T2-hyperintensity 35 , whereas in another study no abnormalities of the main metabolites were detected 36 . Divergent results were also obtained in pathological studies of brain autopsies in which loss of myelin and reduction of the number of myelinated fibres without gliosis were found in one patient 37 , while in two other studies no demyelination, gliosis, or spongy degeneration were detected 38,39 . On the other hand, a MNGIE mouse model showed increased T2 signal in the cerebral white matter on MRI and, at pathological evaluation, multiple vacuoles in subcortical, periventricular, internal capsule and cerebellar white matter without signs of focal demyelination 40 .…”
Section: Discussionmentioning
confidence: 93%